Cathodal HD-tDCS above the left dorsolateral prefrontal cortex increases environmentally sustainable decision-making - Wyss, Annika M.; Baumgartner, Thomas; Guizar Rosales, Emmanuel; Soutschek, Alexander; Knoch, Daria (Frontiers in Human Neuroscience, 2024)
Environmental sustainability is characterized by a conflict between short-term self-interest and longer-term collective interests. Self-control capacity has been proposed to be a crucial determinant of people's ability to overcome this conflict. Yet, causal evidence is lacking, and previous research is dominated by the use of self-report measures. Here, we modulated self-control capacity by applying inhibitory high-definition transcranial current stimulation (HD-tDCS) above the left dorsolateral prefrontal cortex (dlPFC) while participants engaged in an environmentally consequential decisionmaking task. The task includes conflicting and low conflicting trade-offs between short-term personal interests and long-term environmental benefits. Contrary to our preregistered expectation, inhibitory HD-tDCS above the left dlPFC, presumably by reducing self-control capacity, led to more, and not less, pro-environmental behavior in conflicting decisions. We speculate that in our exceptionally environmentally friendly sample, deviating from an environmentally sustainable default required self-control capacity, and that inhibiting the left dlPFC might have reduced participants' ability to do so..